Perfluoroalkyl substances (PFASs) and other halogenated compounds in fish from the upper Labe River basin - Svihlikova, Veronika; Lankova, Darina; Poustka, Jan; Tomaniova, Monika; Hajslova, Jana; Pulkrabova, Jana (Chemosphere, 2015)
This study summarizes results on levels of 25 perfluoroalkyl substances (PFASs), three hexabromocyclododecane isomers (HBCDs), tetrabromobisphenol A (TBBPA), three brominated phenols and four hydroxylated derivates of polybrominated diphenyl ethers (OH-PBDEs) in 59fish samples collected in nine localities on two major rivers from the Czech Republic. To identify potential sources of these chemicals, several sampling sites located close to highly industrialized areas were also involved. The major PFAS representatives, perfluorooctane sulfonate (PFOS), C9-C14 perfluoroalkyl carboxylic acids (PFCAs) and perfluorooctane sulfonamide (FOSA) were detected in 100% fish samples. The concentration ranges of individual substances in the respective groups of PFASs were as follows: 0.572-61.3ngg(-)(1) wet weight (ww) for Tot-PFOS, 0.007-0.121ngg(-)(1)ww for perfluoroalkane sulfonates (PFSAs) (without PFOS isomers), 0.007-22.0ngg(-)(1)ww for PFCAs and 0.026-7.76ngg(-)(1)ww for FOSA. The highest contents of ∑PFASs (51.9ngg(-)(1)ww and 47.8ngg(-)(1)ww) were measured in fish muscle tissue from the locality Trmice situated on the Bílina River and Verdek on the Labe River, where chemical and/or textile industry is located. From 11 targeted BFRs, five compounds (α-HBCD, β-HBCD, γ-HBCD, TBBPA and 2,4,6-tribromophenol (TBP)) were determined in analyzed samples. The concentration ranged as follows: 3.15-1211ngg(-)(1) lipid weight (lw) for ∑HBCD, 4.99-203ngg(-)(1)lw for TBBPA and 1.76-107ngg(-)(1)lw for 2,4,6-TBP.
Keywords: zvířata; monitorování životního prostředí; Animals; Fishes; Czech Republic; řeky; Environmental Monitoring; Česká republika; ryby; Hydrocarbons, Halogenated; Fluorocarbons; chemické látky znečišťující vodu; halogenované uhlovodíky; fluorokarbony; Water Pollutants, Chemical; Rivers